The effect of cold storage and cooking on the viability of Clostridioides difficile spores in consumer foods. (June 2023) - Marcos, Pilar; Glennon, Chloe; Whyte, Paul; Rogers, Thomas R.; McElroy, Máire; Fanning, Seamus; Frias, Jesus; Bolton, Declan
Abstract: The increased detection of clinical cases of Clostridioides difficile coupled with the persistence of clostridial spores at various stages along the food chain suggest that this pathogen may be foodborne. This study examined C. difficile (ribotypes 078 and 126) spore viability in chicken breast, beef steak, spinach leaves and cottage cheese during refrigerated (4 °C) and frozen (−20 °C) storage with and without a subsequent sous vide mild cooking (60 °C, 1 h). Spore inactivation at 80 °C in phosphate buffer solution, beef and chicken were also investigated to provide D80°C values and determine if PBS was a suitable model system for real food matrices. There was no decrease in spore concentration after chilled or frozen storage and/or sous vide cooking at 60 °C. Non-log-linear thermal inactivation was observed for both C. difficile ribotypes at 80 °C in phosphate buffer solution (PBS), beef and chicken. The predicted PBS D80°C values of 5.72±[2.90, 8.55] min and 7.50±[6.61, 8.39] min for RT078 and RT126, respectively, were in agreement with the food matrices D80°C values of 5.65 min (95% CI range from 4.29 to 8.89 min) for RT078 and 7.35 min (95% CI range from 6.81 to 7.01 min) for RT126. It was concluded that C. difficile spores survive chilled and frozen storage and mild cooking at 60 °C but may be inactivated at 80 °C. Moreover thermal inactivation in PBS was representative of that observed in real food matrices (beef and chicken). Highlights: C. difficile RT078 and RT126 spores survive prolonged chilled and frozen storage in different foods. Sous vide cooking at 60 °C for 1 h did not decrease C. difficile spore concentration in spiked meats. A 1.0–1.5 log10 spores/g reduction in C. difficile RT078 and RT126 spores was observed after treatment at 80 °C for 40 min.